Publicaciones políticas y culturales Argentinas, c. 1900-1950 (Anagraphix, 2005)
Consists chiefly of periodicals issued by leftist organizations in Argentina, 1900-1950; also includes some monographic and periodical publications concerning communism in Uruguay and other Latin American countries published in Montevideo, Uruguay and Barcelona, Spain.